2022
DOI: 10.1051/sicotj/2022014
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between clinical and radiological severity of osteoarthritis of the knee

Abstract: Introduction: Primary osteoarthritis (OA) is a common cause of knee pain. Appropriate management of knee OA is based on clinical and radiological findings. Pain, deformity, and functional impairments are major clinical factors considered along with radiological findings when making management decisions. Differences in management strategies might exist due to clinical and radiological factors. This study aims at finding possible associations between clinical and radiological observations. Methods: A prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Finally, systems such as the KL grade fail to capture the range of reported pain and function at various levels of knee joint degeneration [17][18][19][20] . Figure 2 demonstrates this in a violin plot of patient pain compared with KL grade.…”
Section: Model Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, systems such as the KL grade fail to capture the range of reported pain and function at various levels of knee joint degeneration [17][18][19][20] . Figure 2 demonstrates this in a violin plot of patient pain compared with KL grade.…”
Section: Model Evaluationmentioning
confidence: 99%
“…Clinicians may not be as good at this as we think, even when it comes to the first step of determining the degree to which pain originates from structural factors within the knee 15 . Clinicians rely on the Kellgren-Lawrence (KL) grade to gauge the structural severity of osteoarthritis by radiographs 16 , yet the KL grade does not explain pain very well [17][18][19][20] . It is not uncommon for clinicians to see patients with severe degenerative changes on radiographs (high KL grades) and relatively little pain, as well as those with relatively mild degenerative changes on radiographs (low KL grades) and severe pain.…”
mentioning
confidence: 99%
“…Previous studies have widely used the K-L grading system to determine the severity of osteoarthritis, but since most subjects who underwent DLO presented K-L grade 4 changes in this study, the use of the Ahlbäck classification system was able to more effectively differentiate the osteoarthritic severity. In addition, the Ahlbäck classification was better suited for radiological evaluation of this patient population than the K-L classification because it focuses more on joint space narrowing and bone attrition [ 41 ]. In the statistical analysis of this study, improvement in clinical score was less satisfactory in knees with Ahlbäck grade 3 or 4.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, most knees with joint space narrowing that undergo osteotomy are classified as either grade 3 or 4. However, Ahlbäck proposed another radiological classification system for osteoarthritic knees in which K-L grade 4 can be further subdivided into Ahlbäck grades 2–5 [ 3 , 41 ]. Since candidates for DLO present severe varus deformity with apparent joint space narrowing, use of the Ahlbäck classification may provide a clearer relationship between radiological osteoarthritic grade and surgical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis demonstrated significant improvement in pain, movement, and quality of life in the short term, between three and six months [ 26 ]. The United States of America has a relatively young cohort of osteoarthritic patients with more than half, below the age of 60 years [ 28 ]. In our series, patients below 56 years had significant improvement in their OKS.…”
Section: Discussionmentioning
confidence: 99%